Prophylactic Bilateral Salpingectomy as a Prevention Strategy in Women at High-Risk of Ovarian Cancer: A Mini-Review - Schenberg, Tess; Mitchell, Gillian (Frontiers in Oncology, 2014)
Risk-reducing bilateral salpingo-oophorectomy is a proven strategy to reduce the risk of serous ovarian cancer associated with germline BRCA mutations. It is most effective when performed before natural menopause but it will render a woman prematurely menopausal. The tubal hypothesis of serous ovarian cancer brings with it the possibility of the alternative surgical approach in younger women comprising of risk-reducing bilateral salpingectomy while conserving their ovaries until nearer the age of natural menopause when a delayed bilateral oophorectomy can be performed. This article will review the evidence behind the tubal hypothesis of serous ovarian cancer and explore the opportunities for translating this into clinical cancer prevention practice.